2023
DOI: 10.3390/v15030785
|View full text |Cite
|
Sign up to set email alerts
|

EV-A71 Mechanism of Entry: Receptors/Co-Receptors, Related Pathways and Inhibitors

Abstract: Enterovirus A71, a non-enveloped single-stranded (+) RNA virus, enters host cells through three stages: attachment, endocytosis and uncoating. In recent years, receptors/co-receptors anchored on the host cell membrane and involved in this process have been continuously identified. Among these, hSCARB-2 was the first receptor revealed to specifically bind to a definite site of the EV-A71 viral capsid and plays an indispensable role during viral entry. It actually acts as the main receptor due to its ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 165 publications
0
11
0
Order By: Relevance
“…The life cycle of EV-A71 is composed of a series of consecutive events, including virus–receptor binding, receptor-mediated endocytosis, uncoating, viral protein synthesis, RNA genome synthesis, assembly, virus maturation, and release from the host cell. Candidate drugs that inhibit any step in the EV-A71 life cycle may reduce virus production [ 2 ]. The results of Figure 2 , Figure 3 , Figure 4 and Figure 5 demonstrate the impact of the long-term presence of cordycepin on the entire process of the EV-A71 life cycle, thereby inhibiting virus production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The life cycle of EV-A71 is composed of a series of consecutive events, including virus–receptor binding, receptor-mediated endocytosis, uncoating, viral protein synthesis, RNA genome synthesis, assembly, virus maturation, and release from the host cell. Candidate drugs that inhibit any step in the EV-A71 life cycle may reduce virus production [ 2 ]. The results of Figure 2 , Figure 3 , Figure 4 and Figure 5 demonstrate the impact of the long-term presence of cordycepin on the entire process of the EV-A71 life cycle, thereby inhibiting virus production.…”
Section: Discussionmentioning
confidence: 99%
“…Enterovirus A71 (EV-A71) infection is an emerging infectious disease that has become a serious threat to public health around the world in recent years, especially in the Asia-Pacific region [ 1 ]. EV-A71 belongs taxonomically to the genus Enterovirus in the family Picornaviridae [ 2 , 3 ]. The common infectious age groups are infants and young children, and it is transmitted through the fecal–oral route [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystal structure showed that a depression (the “canyon”) encircles the icosahedral fivefold axes of the virions, which was predicted to be the binding site of receptors that have an immunoglobulin-like fold [ 5 ]. Several molecules have been found to act as receptors for EV71 infection, including Scavenger receptor class B member 2 (SCARB2), P-selectin glycoprotein ligand-1(PSGL-1), annexin II, heparan sulfate (HS), etc [ 6 , 7 ]. Among them, SCARB2 is the major function receptor that supports both attachment and uncoating of virions, while others are classified as “attachment receptors” [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%